Metode Dakwah Ustadz Eki Marlinton M A I T ( M Taklim) Nagari Bukit Bual Kabupaten Sijunjung. - Anike, Sintia Putri; Syafriani, Desi (ANTHOR: Education and Learning Journal, 2023)
This research is motivated by the importance of the methods used by a Da'i in preaching. Thepurpose of this study is to find out what methods da'wah Ustadz Eki Marlinton uses in preachingand what obstacles to da'wah he experiences. The type of research used is field research with adescriptive qualitative approach, namely research whose data collection methods are obtainedfrom observation, interviews, and documentation, and data analysis techniques systematicallyselect data obtained from interviews and documentation. The results of the study are the da'wah methods used by Ustadz Eki in preaching, namely the Al-Hikmah method, Mau'idzah Hasanah, and Mujaddalah. Al-Hikmah, namely preaching by mingling with his congregation by making a contract/agreement before preaching and giving a good example to his congregation, Mau'idzatil Hasanah, namely the method of advising by singing and praying to Allah SWT. Mujaddalah method by discussing and doing questions and answers with his congregation. The obstacles to Ustadz Eki Marlinton's da'wah are viewed from several aspects, the first is the Biological aspect, this aspect is viewed from the group of his congregation where in this case the congregation of BKMT is mostly women, the second is the Economic aspect is viewed from the urban or rural community, rich and poor, the third is the Educational Aspect, the level of education greatly affects the style and material of da'wah that will be delivered, if the congregation who has a rank and who does not have a rank, then it will be an obstacle to preaching for him.